Tocilizumab plus dexamethasone versus dexamethasone in patients with moderate-to-severe COVID-19 pneumonia: A randomised clinical trial from the CORIMUNO-19 study group. (April 2022) - Hermine, Olivier; Mariette, Xavier; Porcher, Raphael; Djossou, Felix; Nguyen, Yann; Arlet, Jean-Benoît; Savale, Laurent; Diehl, Jean Luc; Georgin-Lavialle, Sophie; Cadranel, Jacques; Pialoux, Gilles; Lacombe, Karine; et al.
Summary: Background: In moderate-to-severe COVID-19 pneumonia, dexamethasone (DEX) and tocilizumab (TCZ) reduce the occurrence of death and ventilatory support. We investigated the efficacy and safety of DEX+TCZ in an open randomized clinical trial. Methods: From July 24, 2020, through May 18, 2021, patients with moderate-to-severe COVID-19 pneumonia requiring oxygen (>3 L/min) were randomly assigned to receive DEX (10 mg/d 5 days tapering up to 10 days) alone or combined with TCZ (8 mg/kg IV) at day 1, possibly repeated with a fixed dose of 400 mg i.v. at day 3. The primary outcome was time from randomization to mechanical ventilation support or death up to day 14, analysed on an intent-to-treat basis using a Bayesian approach. ClinicalTrials.gov number, NCT04476979. Findings: A total of 453 patients were randomized, 3 withdrew consent, 450 were analysed, of whom 226 and 224 patients were assigned to receive DEX or TCZ+DEX, respectively. At day 14, mechanical ventilation or death occurred in 32/226 (14%) and 27/224 (12%) in the DEX and TCZ+DEX arms, respectively (hazard ratio [HR] 0·85, 90% credible interval [CrI] 0·55 to 1·31). At day 14, the World health Organization (WHO) clinical progression scale (CPS) was significantly improved in the TCZ+DEX arm (OR 0·69, 95% CrI, 0·49 to 0.97). At day 28, the cumulative incidence of oxygen supply independency was 82% in the TCZ+DEX arms and 72% in the DEX arm (HR 1·36, 95% CI 1·11 to 1·67). On day 90, 24 deaths (11%) were observed in the DEX arm and 18 (8%) in the TCZ+DEX arm (HR 0·77, 95% CI 0·42–1·41). Serious adverse events were observed in 25% and 21% in DEX and TCZ+DEX arms, respectively. Interpretation: Mechanical ventilation need and mortality were not improved with TCZ+DEX compared with DEX alone. The safety of both treatments was similar. However, given the wide confidence intervals for the estimate of effect, definitive interpretation cannot be drawn. Funding: Programme Hospitalier de Recherche Clinique [PHRC COVID-19–20–0151, PHRC COVID-19–20–0029], Fondation de l'Assistance Publique – Hôpitaux de Paris (Alliance Tous Unis Contre le Virus) and from Fédération pour la Recherche Médicale" (FRM). Tocilizumab was provided by Roche.